Математична модель реології фрактально-неоднорідних пластових систем - Положаєнко, Сергій Анатолійович; Савіч, Віталій Святославович (Kamianets-Podilskyi National Ivan Ohiienko University, 2016)
The conditions of «smoothness» of heterogeneous components Front separation (heterogeneous) systems by analyzing the «jump» feature in saturation Bakley-Leverett. It is shown that «jump» saturation absent, and the division front was moving and keeps the «smoothness» when the movable components that squeezes does not exceed movable components that squeezed. Also show that violations of the «smoothness» Front separation leads to inhomogeneous fractal structure process rheology. A numerical values fractal dimension of the front division for rheological process that occurs in real geological conditions. The mathematical model of fractal-heterogeneous systems in a class of varitional inequalities.